The assessment of the nutrient content in the plants of the hybrid Sorghum bicolor x Sorghum sudanense harvested in different development stages - Țiței, Victor; Coșman, Sergiu; Cîrlig, Natalia; Coșman, Valentina; Guțu, Ana; Mocanu, Natalia; Cozari, Serghei; Teleuță, Alexandru; Garștea, Nina (Acta et Commentationes Exact and Natural Sciences, 2023)
The article presents the results of the research aimed at evaluating the nutrient content in the leaves, stems and panicles of the hybrid sorghum x Sudan grass “SAȘM-4” plants harvested in different development stages. It has been determined that the leaves have a higher content of crude protein, crude fat, carotene, ash, calcium and phosphorus; the stems have a high content of crude cellulose, nitrogen-free extract and sugar; while the panicles are rich in starch, with high energy value. During the growing season, in all component parts, the content of dry matter increases, the concentration of proteins decreases and the content of cellulose and nitrogen-free extract essentially increases.